Hypertensive disorders of pregnancy and neonatal outcomes in twin vs. singleton pregnancies after assisted reproductive technology - Liu, Ting; Gao, Rui; Liu, Yong; Zhao, Ke; Su, Xiaolin; Wong, Hin Ching; Li, Luyao; Xie, Binbin; Huang, Yuanyan; Qiu, Chuhui; He, Jiang; Liu, Chaoqun (Frontiers in Pediatrics, 2022)
Objective: Hypertensive disorders of pregnancy (HDP) are associated with an increased risk of adverse neonatal outcomes. Although twin pregnancies had a higher risk of developing HDP, it is not known whether HDP in twins will increase the risk of adverse neonatal outcomes. We aimed to assess whether this association differed in singleton and twin pregnancies in women who conceived with assisted reproductive technology (ART). Methods: We finally included 193,590 live births born via ART from the National Vital Statistics System (NVSS) for the years 2015-2019. We used Log-binomial regression to evaluate the associations between HDP and the risk of adverse neonatal outcomes in ART mothers. Results: Among 193,590 ART-treated mothers, there were 140,870 and 52,720 mothers who had singleton pregnancies and twin pregnancies, respectively. Those ART mothers with twin pregnancies had a higher rate of HDP than singleton pregnancies (20.5% vs. 11.0%). In singleton pregnancies, the risks of preterm birth (adjusted risk ratio (aRR): 2.80, 95% CI 2.67-2.93), low birth weight (aRR: 2.80, 95% CI 2.67-2.93), small for gestational age (aRR: 1.41, 95% CI 1.34-1.49), five-minute Apgar < 7 (aRR: 1.66, 95% CI 1.50-1.83) and cesarean section (aRR: 1.23, 95% CI 1.21-1.25) were significantly higher in HDP mothers than in non-HDP mothers respectively. However, in contrast to singleton pregnancies, these associations were weak or reversed in twin pregnancies, after adjusting for confounding factors. Conclusion: In ART-treated women, although twin pregnancies had a higher HDP rate, the risk of adverse neonatal outcomes associated with HDP was lower than that of singletons.